Urban Forest Management: A Primer to Strategic Planning for Municipal Governments: FOR387/FR458, 12/2022 - Andreu, Michael; Northrop, Robert; Zipperer, Wayne (EDIS, 2022)
This publication is an introduction to Urban Forest Management: A Primer to Strategic Planning for Municipal Governments, available in full for free here: https://ffgs.ifas.ufl.edu/urbanforestmanagementbook/.